Spontaneous Pulmonary Alveolar Proteinosis in Captive "Moustached Tamarins" (Saguinus mystax) (Primates: Callitrichidae) - Michaud, Carmen R. (Vet Pathol, 2011)
Pulmonary alveolar proteinosis (PAP) is a rare human disease characterized by accumulation of surfactant in alveoli without generating an inflammatory response. Lung lesions resembling PAP were observed in seven adult tamarins (five males and two females). Gross lesions were characterized by areas of discoloration, slight bulging over the lung parenchyma, and occasional consolidation. Histological examination of tamarin lung samples revealed intra-alveolar accumulation of an amorphous, amphophilic, PAS-positive, finely granular to dense material. In some cases type II pneumocyte hypertrophy and hyperplasia with pleural and septal thickening and fibrosis were observed. Large numbers of intra-alveolar foamy macrophages were noted surrounding and/or in the vicinity of the lesions. Immunohistochemical analysis of the lung lesions using polyclonal (surfactant proteins A, B, and C) and monoclonal (surfactant protein D) antibodies revealed the granular material to be composed largely of surfactant protein B, followed by surfactant protein A. Surfactant proteins C and D (SP-D) were present in lesser quantities; with SP-D observed surrounding the lipoproteinaceous deposits. Transmission electron microscopy of the affected lungs showed numerous, irregularly-shaped, osmiophilic lamellar bodies in type II pneumocytes. The cytoplasm in alveolar macrophages was expanded, containing ingested surfactant with swollen mitochondria and rough endoplasmic reticulum. Thoracic radiographs, available in one animal, depicted the lesions as small multifocal opacities randomly distributed in cranial and diaphragmatic lung lobes. This is, to our knowledge, the first report of spontaneous PAP in nonhuman primates.